2015
DOI: 10.1007/s10368-015-0326-y
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of common rules of origin on FTA utilization

Abstract: This paper examines empirically the impacts of sharing rules of origin (RoOs) with other ASEAN+1 free trade agreements (FTAs) on ASEAN-Korea FTA/ASEAN-China FTA utilization in Thai exports in 2011. Our careful empirical analysis suggests that the harmonization of RoOs across FTAs play some role in reducing the costs yielded through the spaghetti bowl phenomenon. In particular, the harmonization to "change-in-tariff classification (CTC) or real value-added content (RVC)" will play a relatively positive role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…We use average tariff rates, as tariff schedules are aggregated from the HS-10 level to the HS-6 level to match the customs clearance data (a summary of the average applied tariff rates on imports from ASEAN to Australia is provided in the Annex). Hayakawa and Laksanapanyakul (2017) find that the decision to aggregate preference margins based on minimums, maximums, or means has little effect on research outcomes.…”
Section: A Data and Methodologymentioning
confidence: 85%
See 2 more Smart Citations
“…We use average tariff rates, as tariff schedules are aggregated from the HS-10 level to the HS-6 level to match the customs clearance data (a summary of the average applied tariff rates on imports from ASEAN to Australia is provided in the Annex). Hayakawa and Laksanapanyakul (2017) find that the decision to aggregate preference margins based on minimums, maximums, or means has little effect on research outcomes.…”
Section: A Data and Methodologymentioning
confidence: 85%
“…Based on similar customs data, studies find a positive impact of FTA utilization on Korean imports from ASEAN under the ASEAN-Korea FTA (Hayakawa et al, 2013a(Hayakawa et al, , 2014 and on Thailand's imports under its FTAs (Hayakawa & Laksanapanyakul, 2017). Recent studies by Ando and Urata (2018) and Hayakawa and Shiino (2021) highlight the positive impact of FTAs on imports for Japanese FTAs.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…This article contributes to the small, but growing, literature on the impact of rules of origin on trade. For example, several studies use cross‐sectional data to analyze how utilization rates differ across trade agreements (Cadot et al, 2006; Hakobyan, 2015; Hayakawa & Laksanapanyakul, 2017). Other studies find that utilization rates grow as the difference between preferential and non‐preferential tariff rates grow (Francois et al, 2005; Keck & Lendle, 2012; Manchin, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Hayakawa et al (2014) suggested that the restrictive ROOs should be relaxed to create more trade flows between members of the AKFTA. Similarly, Hayakawa and Laksanapanyakul (2017) conducted a rigorous econometric estimation analysis to investigate the impact of ROOs in ASEAN+1 FTAs including the AKFTA, and strongly recommended harmonizing the ROOs across the ASEAN+1 FTAs.…”
Section: Introductionmentioning
confidence: 99%